Reducing blood product wastage: Insights from a retrospective study in a tertiary health facility - Jawaher Alsughayyir; Afnan Alghamdi; Abdulaziz M. Almuqrin; Abdulrahman Alshalani; Nasser Alqahtani; Ammar Alsughayir; Alyazeed Alsaif; Yazeed Alfalah; Sarah Bakr Abobakr; Naif Bin Muhannaa; Fahad Alshehri (PLoS ONE, 2026)
Introduction Due to the absence of prior institutional assessments and limited local studies lacking key performance indicators, this study examines the operational efficiency of the blood bank at King Fahad Medical City (KFMC) in Riyadh, Saudi Arabia, and aims to identify inefficiencies in blood ordering practices and recommend corrective measures. Methods This retrospective study analyzed KFMC blood bank inventory data from January 2022 to December 2023, using descriptive statistics and three key performance indicators: the crossmatch-to-transfusion ratio (C/T), wastage as a percentage of issue (WAPI), and the issuable stock index (ISI). Results Overall, 95.05% of blood products were utilized, 3.8% were returned in acceptable condition, 4.2% expired, and 0.6% were discarded for non-expiry-related reasons. The C/T ratio was 1.5, the ISI was maintained at 1.1 across all blood groups, and WAPI remained below 1.2%, indicating efficient inventory management. Discussion Blood bank management at KFMC demonstrated strong operational efficiency through strategic inventory management. Most post-crossmatch wastage resulted from over-ordering in high-demand areas such as the intensive care unit, reflecting the urgency of these settings. Regular audits and updates to the Maximum Surgical Blood Ordering Schedule are recommended to optimize efficiency and minimize waste. This study provides a valuable benchmark for future research on blood bank operations and inventory management.